In silico identification and evaluation of new Trypanosoma cruzi trypanothione reductase (TcTR) inhibitors obtained from natural products database of the Bahia semi-arid region (NatProDB). (April 2019) - da Paixão, Vinícius Guimarães; Pita, Samuel Silva da Rocha
Graphical abstract: Highlights: Chagas' disease since 1909 has any effective treatment for chronic phase. Trypanosoma cruzi Trypanothione Reductase (TcTR) is a validated target for Chagas' disease. Brazil's biodiversity was not fully explored mainly at Semi-arid regions. NatProDB has catalogued the chemical compounds of Bahia Semi-arid regions. Docking, Pharmacokinetic and Toxicological analysis selected novel anti-chagasic. Abstract: Trypanosoma cruzi Trypanothione Reductase (TcTR) is one of the therapeutic targets studied in the development of new drugs against Chagas' disease. Due to its biodiversity, Brazil has several compounds of natural origin that were not yet properly explored in drug discovery. Therefore, we employed the Virtual Screening against TcTR aiming to discover new inhibitors from the Natural Products Database of the Bahia Semi-Arid region (NatProDB). This database has a wide chemical diversity favoring the discovery of new chemical entities. Subsequently, we analyzed the best docking conformations using self-organizing maps (AuPosSOM) aiming to verify their interaction sites at TcTR. Finally, the Pred-hERG, the Aggregator Advisor, the FAF-DRUGS and the pkCSM results allowed us to evaluate, respectively, the cardiotoxicity, aggregation capacity, presence of false positives (PAINS) and its toxicity. Thus, we selected three molecules that could be tested in in vitro assays in the hope that the computational results reported here would favor the development of new anti-chagasic drugs.